Economic development - Todaro, M. P.; Smith, Stephen C., 1955- (Hoboken : Pearson, 2020)
'Economic Development, Twelfth Edition, presents the latest thinking in economic development with the clear and comprehensive approach that has been so well received in both the developed and developing worlds. The pace and scope of economic development continues its rapid, uneven, and sometimes unexpected evolution. This text explains the unprecedented progress that has been made in many parts of the developing world but fully confronts the enormous problems and challenges that remain to be addressed in the years ahead. The text shows the wide diversity across the developing world and the differing positions in the global economy that are held by developing countries. The principles of development economics are key to understanding how we got to where we are, how great progress has been made in recent years, and why many development problems remain so difficult to solve. The principles of development economics are also key to the design of successful economic development policy and programs as we look ahead. The field of economic development is versatile and has much to contribute regarding these differing scenarios. Thus, the text also underlines common features that are exhibited by a majority of developing nations, using the insights of the study of economic development. The few countries that have essentially completed the transformation to become developed economies, such as South Korea, are also examined as potential models for other developing countries to follow. Both theory and empirical analysis in development economics have made major strides, and the Twelfth Edition brings these ideas and findings to students. Legitimate controversies are actively debated in development economics, and so the text presents contending theories and interpretations of evidence, with three goals. The first goal is to ensure that students understand real conditions and institutions across the developing world. The second is to help students develop analytic skills while broadening their perspectives of the wide scope of the field. The third is to provide students with the resources to draw independent conclusions as they confront development problems, their sometimes ambiguous evidence, and real-life development policy choices-ultimately, to play an informed role in the struggle for economic development and ending extreme poverty'--
Revised edition of the authors' Economic development, [2015]
Includes bibliographical references and index.
Keywords: Economic development; Developing countries -- Economic policy